Surface Electromyography-based Gesture Recognition for Robot Hand Control - Savić, Srđan; Pavlović, Dunja; Čilag, Andrej (Journal of Computer and Forensic Sciences, 2024)
This paper presents a human-machine interaction interface for a teleoperated control of a three-finger robot hand based on a surface electromyography. Based on the recorded sEMG signals, motion intention of a human operator is recognized and mapped onto corresponding predefined robot hand grasps. First, the experimental setup and underlying methodology of dataset generation are presented. Namely, 4-channel EMG data were collected from the forearm muscles of 4 healthy subjects as they performed a sequence of predefined grasps. Data processing included: data filtering and segmentation, feature extraction both in time and frequency domains, data annotation, and gestures classification. Two types of classifiers (with multiple variations of parameters) were implemented and compared: (i) Support Vector Machines with multiple different kernels and (ii) K-Nearest-Neighbors. The k-cross validation procedure was combined with the holdout method to generate training, validation and test sets. Performance of each classifier is presented in the form of a confusion matrix and a set of statistical measures, including F-measure. Finally, the integration of the proposed sEMG-based HMI interface and the selected classifier with a robot hand motion controller is presented.